Gust Modeling with State-of-the-Art Computational Fluid Dynamics (CFD) Software and Its Influence on the Aerodynamic Characteristics of an Unmanned Aerial Vehicle - Michał Frant; Stanisław Kachel; Wojciech Maślanka (Energies, 2023)
The aim of this article is to propose methods for obtaining the aerodynamic characteristics of a flying object in a turbulent atmosphere. This article presents static aerodynamic characteristics of an unmanned aerial vehicle (UAV), which have been obtained during experimental examinations and during numerical calculations. The results have been compared with each other in order to validate the numerical model and methods. The method for modeling gusts using state-of-the-art CFD software (i.e., ANSYS Fluent Release 16.2) has been proposed and applied to obtain the aerodynamic characteristics of a UAV including during gusts. Two cases have been analyzed. In the first case, a downburst was modeled. In the second case, a single oblique gust was modeled (i.e., changing the angle of attack and the angle of sideslip), that had a complicated time course in regard to its velocity. Although this article is focused on the assessment of the vulnerability of a UAV model to gusts, the practical implications of the proposed methodology are applicable to a wide selection of objects, including wind turbines.